Pembelajaran Tari Jamuran sebagai Stimulasi Motorik Kasar pada Komunitas Cinta ABK di Puskesmas Sukomulyo Kabupaten Gresik: stimulasi motorik kasar untuk anak berkebutuhan khusus - Rachel Tahta Maulida Rachel; Welly Suryandoko (Jurnal Pendidikan Sendratasik, 2026)
Children with Special Needs (ABK) require special treatment not only in medical aspects, but also psychosocial and motor aspects. In Sukomulyo Health Center, Gresik Regency, there is a forum called "ABK Love Community" which houses parents and special children. The partner's problem is the lack of variety of therapeutic activities that are recreational and preserve local culture, where activities are often focused on monotonous medical therapy. This community service offers a solution in the form of learning the "Jamuran" Dolanan Dance. The Jamuran Dance was chosen because it contains elements of gross motor movements (walking in circles, holding hands, squatting, standing) and intense social interaction. The implementation method of this community service includes: (1) Preparation and location survey, (2) Socialization to parents/community, (3) Training and mentoring of dance movements (fieldwork), and (4) Evaluation and simple performances. The learning process is carried out with a joyful learning approach (fun learning) and repetition (repetition) considering the diverse characteristics of ABK (Autism, Down Syndrome, Mental Retardation). The results of this community service show an increase in children's enthusiasm for movement, gross motor skills that are more stimulated through the dynamic movements of the Jamuran dance, as well as increased emotional bonds between children, parents, and peers. The Jamuran dance has proven effective as a fun, local culture-based alternative therapy medium for the ABK Love Community at the Sukomulyo Community Health Center.